Experience in the Organization of the Neuropsychological Support of Children with Mental Retardation in Comprehensive Secondary Schools - Zhuikova, S; Lukianova, T (KnE Life Sciences, 2018)
Over the years, the neuropsychological approach has proven its validity and effectiveness as a differential-diagnostic, prognostic, preventive and corrective tool for working with different groups of children. But it has not yet entered the wide practice of teachers and psychologists of secondary schools. The purpose of our work is the organization of neuropsychological support of children with mental retardation in a secondary school. As a result of neuropsychological diagnostics for each first grader the individual neuropsychological profile is made. The main directions of correction work are defined and realized. The main attention is paid to the development of spatial notions, which are key in teaching reading, writing and counting. As a result, the positive dynamics in the development of all levels of spatial notions – from the notions of the body to quasi-dimensional notions - is shown. This helped children overcome their training maladjustment. As a result of our work, it has also become possible to achieve the introduction of neuropsychological support in the daily educational process, to provide school teachers with basic algorithms of neuropsychological support of learning processes. Keywords: neuropsychological support, mental retardation, spatial notions